Profiling the physicochemical and solid state properties of edible Tetracarpidium conophorum oil and its admixtures for drug delivery - Chukwuebuka Emmanuel Umeyor; Faithline Dan-Ejih; Amarachukwu Ukamaka Okonkwo; Immaculeta Chikamnele Umeyor; Anthony Amaechi Attama (Universidade de São Paulo, 2022)
Abstract The study is aimed at investigating the functional physicochemical and solid state characteristics of food-grade Tetracarpidium conophorum (T. conophorum) oil for possible application in the pharmaceutical industry for drug delivery. The oil was obtained by cold hexane extraction and its physicochemical properties including viscosity, pH, peroxide, acid, and thiobarbituric acid values, nutrient content, and fatty acid profile were determined. Admixtures of the oil with Softisan®154, a hydrogenated solid lipid from palm oil, were prepared to obtain matrices which were evaluated by differential scanning calorimetry, fourier-transform infrared spectroscopy, and x-ray diffractometry. Data from the study showed that T. conophorum oil had Newtonian flow behaviour, acidic pH, insignificant presence of hyperperoxides and malondialdehyde, contains minerals including calcium, magnesium, zinc, copper, manganese, iron, selenium, and potassium, vitamins including niacin (B3), thiamine (B1), cyanocobalamine (B12), ascorbic acid (C), and tocopherol (E), and long-chain saturated and unsaturated fatty acids including n-hexadecanoic acid, 9(Z)-octadecenoic acid, and cis-13-octadecenoic acid. The lipid matrices had low crystallinity and enthalpy values with increased amorphicity, and showed no destructive intermolecular interaction or incompatibility between T. conophorum oil and Softisan® 154. In conclusion, the results have shown that, in addition to T. conophorum oil being useful as food, it will also be an important excipient for the development of novel, safe, and effective lipid-based drug delivery systems.